Notes on the notions of 'communication' and 'intention' and the status of speaker and addressee in linguistics - Scheppers, Frank (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Notes on the notions of 'communication' and 'intention' and the status of speaker and addressee in linguistics